Atmospheric lead concentrations near roadways in a suburban part of Istanbul - Karaca, Ferhat; Alagha, Omar; Erturk, Ferruh (INDERSCIENCE ENTERPRISES LTD, 2010)
In this study, daily aerosol samples of fine (PM(2.5)) and coarse (PM(2.5-10)) particles were collected at Bilytikcekmece (41 degrees 2'35 '' N, 28 degrees 35'25 '' E), a sub-urban part of Istanbul, Turkey. Sampling area is under the impact of two main transport arteries, namely the Trans European Motorway (TEM) and E5 motorways. Atmospheric lead levels measured in this study were compared with those reported previously from various locations in Turkey and other parts of the world. These values lie midway between those typical of remote and urban sites. The data were statistically evaluated to determine seasonal changes. Then, wind sector analysis was carried out. The analysis showed that the major proportion of the episodes, about 54%, was generated from the direction of TEM motorway, located to the north, while the second major lead source, with a contribution of 20%, was found to be the direction of E-5 motorway, located to the south.
Keywords: atmospheric lead; fine and coarse particles; air quality; atmospheric emissions; meteorology; AIRBORNE PARTICULATE MATTER; CAPE GRIM; POLLUTION; TURKEY; AIR; PM10; PM2.5; SWITZERLAND; GASOLINE; TASMANIA; Environmental Sciences & Ecology